Du sang à l’encre : l’empereur Julien, superstitiosus ou piissimus imperator ? - Dario Cellamare (Mythos, 2023)
Ink and blood seem to be the core-elements of Julian’s brief reign (361-363), with whom his hands would be ever covered. As a sort of synecdoche, these two elements could summarize the most famous activities of the emperor: his literary works and his sacrifices. Though, since his death lots of ink have been spilled about blood ‘spilled’ by Julian: from Late antiquity until now, many works depict him as a ‘obsessive-compulsive sacrifice performer’, increasingly obsessed with bizarre rituals, isolated from the rest of the population. Reconsidering several ancient sources, aim of this paper is to verify whether Julian’s cult practice was in the wake of the customary rites of the Roman tradition, of which he was the most scrupulous interpreter (piissimus); or if, on the other hand, his actions were an anomaly, out of reality, beyond the norm and beyond the correct way to address to divine powers (superstitiosus). Therefore, I will discuss the stereotype of Julian as the ‘last of the Mohicans of paganism’ and its historiographical background, such as the so-called end of sacrifice during the 4th century.